2018
DOI: 10.1525/elementa.302
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric Ozone Assessment Report: Present-day tropospheric ozone distribution and trends relevant to vegetation

Abstract: This Tropospheric Ozone Assessment Report (TOAR) on the current state of knowledge of ozone metrics of relevance to vegetation (TOAR-Vegetation) reports on present-day global distribution of ozone at over 3300 vegetated sites and the long-term trends at nearly 1200 sites.TOAR-Vegetationfocusses on three metrics over vegetation-relevant time-periods across major world climatic zones: M12, the mean ozone during 08:00–19:59; AOT40, the accumulation of hourly mean ozone values over 40 ppb during daylight hours, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
218
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 288 publications
(224 citation statements)
references
References 85 publications
3
218
1
2
Order By: Relevance
“…At the national scale, the countries identified as having the largest potential effects of ozone (e.g. the United States, India and China) match those with the highest monitored ozone concentrations (Mills, Pleijel et al., ) as well as those predicted using concentration‐based approaches to have the highest potential yield losses (Avnery et al., ,b; Van Dingenen et al., ). At the subnational scale, however, there were some differences in areas predicted to be at risk, where our stomatal uptake modelling method took into account the modifying effects of climate and soil moisture on ozone uptake rather than simply predicting the largest effects in the areas with the highest ozone concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the national scale, the countries identified as having the largest potential effects of ozone (e.g. the United States, India and China) match those with the highest monitored ozone concentrations (Mills, Pleijel et al., ) as well as those predicted using concentration‐based approaches to have the highest potential yield losses (Avnery et al., ,b; Van Dingenen et al., ). At the subnational scale, however, there were some differences in areas predicted to be at risk, where our stomatal uptake modelling method took into account the modifying effects of climate and soil moisture on ozone uptake rather than simply predicting the largest effects in the areas with the highest ozone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…40% for major ozone precursors such as NOx, VOC and CO being made between 1990 and 2013 (Maas & Grennfelt, ). These cuts have been associated with significant decreasing trends in the concentration‐based metric AOT40 at 26% and 11% of monitoring sites in wheat‐growing areas of NAM and EUR, respectively, over the period 1995–2014 (Mills, Pleijel et al., ), although the dominant trend for EUR remains “no change.” Over the same time period, increases in precursor emissions of 20%–30% in other areas of the world, including by 50% in India and China, have led to increases in ozone concentration in these regions (Maas & Grennfelt, ). For example, there has been a significant increase in ozone concentration at nearly 50% of wheat‐growing monitoring sites in EAS, with average annual increases in AOT40 at these sites being in the range 300–700 ppb h/y over the period 1995–2014 (Mills, Pleijel et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tropospheric ozone (O 3 ) is recognized as a significant phytotoxic air pollutant (Grulke & Heath, ). The background level of O 3 concentration is constantly increasing due to increased human activity since the pre‐industrial age (Mills et al, ). Once O 3 has entered the leaf, it is dissolved in the apoplast and converted into reactive oxygen species (ROS), which cause a damage to physiological and biochemical processes in the plant leaves (Paoletti, ).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of compiled data sets from many experiments has shown a wide range in ozone sensitivity between different crops, based on ozone concentration (Mills et al, ; Mills & Harmens, ; Mills, Sharps, Simpson, Pleijel, Broberg, et al, ). Model‐based studies using dose‐response functions from such data sets have indicated potential crop yield reductions due to ozone across wide regions of the world (Avnery, Mauzerall, Liu, & Horowitz, ; Mills, Pleijel, et al, ; Mills, Sharps, Simpson, Pleijel, Broberg, et al, ; Mills, Sharps, Simpson, Pleijel, Frei, et al, ; Van Dingenen et al, ). Experimental investigations have shown impacts of ambient ozone concentrations on a wide range of crop species in Europe and the USA by comparing responses of plants in filtered air to those in non‐filtered air (De Temmerman, Legrand, & Vandermeiren, ; Marzuoli, Finco, Chiesa, & Gerosa, ; Pleijel, Broberg, Uddling, & Mills, ).…”
Section: Introductionmentioning
confidence: 99%